2023
DOI: 10.1177/03611981231171914
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Inequity of Transit and Automobile Access Gap across America for Underserved Population

Abstract: This study examines the correlates of the Modal Access Gap (MAG) between transit and automobile to employment opportunities in the 45 most populated American metropolitan areas by testing spatial lag regression models and employing the bivariate local indicator of spatial autocorrelation (BiLISA) at the census block group geographical level. Four findings are discerned. First, MAG is positive regardless of the metropolitan area and travel-time threshold and ranges from 0.22 to 0.98. This indicates transit trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Here, we introduce the BARG index, a similar index to the modal access gap (Maharjan et al 2023, Janatabadi et al 2022, to measure the standardized difference between high-stress bike access (A LTS 4 ) and low-stress bike access (A LTS 1 ) to employment opportunities. Mathematically represented in equation ( 1), BARG is:…”
Section: Methodsmentioning
confidence: 99%
“…Here, we introduce the BARG index, a similar index to the modal access gap (Maharjan et al 2023, Janatabadi et al 2022, to measure the standardized difference between high-stress bike access (A LTS 4 ) and low-stress bike access (A LTS 1 ) to employment opportunities. Mathematically represented in equation ( 1), BARG is:…”
Section: Methodsmentioning
confidence: 99%
“…While public transit, e-bikes or improved walkability are solutions that may be appropriate in some areas, personal vehicles offer unique convenience and agency [39] and are likely to remain an essential form of transportation for many people. Furthermore, studies have demonstrated inequities in public transit [40][41][42] and micro-mobility [43], suggesting that these solutions alone would not result in equitable transportation access.…”
Section: Equitable Technology Accessmentioning
confidence: 99%